Households' willingness to pay for the restoration of degraded forest: empirical evidence from Dengego model tree-based restoration project site, Haramaya District, Ethiopia - Kindineh Sisay; Tessema Toru (Cogent Economics & Finance, 2023)
Forests are admitted as a home for many inestimable goods and services that have an economic value for people living around. However, now a day, due to unsustainable utilization, different destructive human activities and natural phenomena's, most forest resources and their benefits become highly deteriorated from time to time. Hence, this study aimed in estimating households' willingness to pay for the intervention of forest restoration is found to be a vital step for priority setting in its sustainable management. For doing so, data's were collected from 226 randomly selected households of Haramaya district, Oromia National Regional State, Ethiopia. For analyzing the collected data, descriptive statistics, inferential statistics and econometric models such as, bivariate probit and seemingly unrelated bivariate probit models were used. The result from 221 valid responses showed that 196 (88.69%) households were willing to contribute for the restoration whereas the remaining 25 (11.31%) households were not. This asserts that the proposed intervention was highly accepted by the majority of the sampled households hence they are more willing to sustain it. Following the seemingly unrelated bivariate probit parameter estimate, the mean WTP was about 439 Ethiopian birr per year, per household. Accordingly, by using this mean willingness to pay value, the welfare gain from the intervention (forest restoration and its management) for the study district (Haramaya) was computed to be 23,269,634 Ethiopian birr per year. Moreover, as the bivariate probit model results indicate, the probability of willingness to pay was positively and significantly affected by variables such as, sex, frequency of extension contact, land certificate, livestock holding, and slope of the land whereas, age, off/non-farm income, initial bid value (bid1), size of own land and farm experience affected willingness to pay negatively and significantly. Hence, to improve the participation level of the households, policy makers should target on these variables.
Keywords: 330; Bivariate probit; forest restoration; Haramaya; Oromia; seemingly unrelated bivariate probit; willingness to pay